Combined Transverse Steel-External FRP Confinement Model for Rectangular Reinforced Concrete Columns - Al-Rahmani, A.; Rasheed, Hayder A. (My University, 2016)
Recently, the need to increase the strength of reinforced concrete members has become a subject that civil engineers are interested in tackling. Of the many proposed solutions, fiber-reinforced polymer (FRP) materials have attracted attention due to their superior properties, such as high strength-to-weight ratio, high energy absorption and excellent corrosion resistance. FRP wrapping of concrete columns is done to enhance the ultimate strength due to the confinement effect, which is normally induced by steel ties. The existence of the two confinement systems changes the nature of the problem, thus necessitating specialized nonlinear analysis to obtain the column's ultimate capacity. Existing research focused on a single confinement system. Furthermore, very limited research on rectangular sections was found in the literature. In this work, a model to estimate the combined behavior of the two systems in rectangular columns is proposed. The calculation of the effective lateral pressure is based on the Lam and Teng model and the Mander model for FRP wraps and steel ties, respectively. The model then generates stress-strain diagrams for both the concrete core and the cover. The model was developed for the analysis in extreme load events, where all possible contributions to the column's ultimate capacity should be accounted for without any margin of safety. The model was validated against experiments, and the results obtained showed good agreement with almost all of the available experimental data.
Citation: Al-Rahmani, A., & Rasheed, H. (2016). Combined Transverse Steel-External FRP Confinement Model for Rectangular Reinforced Concrete Columns. Fibers, 4(1), 25. doi:10.3390/fib4010008
Keywords: Rectangular Concrete Columns; Fiber-Reinforced Polymer; Confinement; Materials Science